1987
DOI: 10.1063/1.452465
|View full text |Cite
|
Sign up to set email alerts
|

Electronic states and geometries of small Be clusters

Abstract: Ab initio calculations were carried out on all regular geometric configurations of beryllium clusters containing three through seven atoms. Restricted Hartree-Fock, unrestricted Hartree-Fock, and fourth-order Mlhller-Plesset perturbation theory (MP4) using a 6-31G basis set were used to study singlet, triplet, and quintet spin states of each cluster. The septet state of the most stable nuclear configuration of Be 7 was also examined using unrestricted Hartree-Fock theory. In addition, Be 4 was examined as a pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

1987
1987
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 36 publications
1
17
0
Order By: Relevance
“…Marino and Ermler 20 reported the MP4/6-31G bond distances to be 2.040 and 2.116 Å, respectively. Whiteside et al 21 reported the SCF bond distances are 2.028 and 2.099 Å. Lee et al 15 determined that the CCSD/7s3p2d optimized bond distances are both 2.079 Å.…”
Section: Resultsmentioning
confidence: 98%
“…Marino and Ermler 20 reported the MP4/6-31G bond distances to be 2.040 and 2.116 Å, respectively. Whiteside et al 21 reported the SCF bond distances are 2.028 and 2.099 Å. Lee et al 15 determined that the CCSD/7s3p2d optimized bond distances are both 2.079 Å.…”
Section: Resultsmentioning
confidence: 98%
“…27 Study of Be 4 was originally motivated by the prediction of ab initio computations that it would form the smallest significantly bound beryllium cluster. 21,27,36,55,56,58 The dissociation energy also shows a large basis set dependence. 21,27,36,55,56,58 The dissociation energy also shows a large basis set dependence.…”
Section: Introductionmentioning
confidence: 99%
“…The nature of the evolution of crystal properties, from packing of atoms, has been a topic interest for many years 6–17. The investigation of changes in various structural and electronic properties of these systems with crystal growth and the number of atoms necessary to reproduce a complete tri‐periodic system have been the subject of many studies.…”
Section: Introductionmentioning
confidence: 99%